Impact of Parental History of Myopia on the Development of Myopia in Mainland China School-Aged Children. (January 2014) - Lim, Lik Thai; Gong, Yanhong; Ah-Kee, Elliott Y.; Xiao, Gexin; Zhang, Xiulan; Yu, Shicheng
Background: Myopia is a very common condition and a significant public health problem in China. The objective of the study was to explore the genetic influence on myopia in Mainland China school-aged children in Beijing. Methods: In 2008, the data from 15, 316 Chinese school students aged 6–18 years from 19 randomized schools in Beijing were analyzed to evaluate genetic influence on myopia in children. Heritability was calculated by mid-parent–offspring regression and parent–offspring regression. Results: The estimate of heritability was 0.30 (95% CI, 0.27–0.33) for refractive value (RV). The adjusted mean refractive error was –2.33D (95% CI, –2.45 to –2.21) in children with two myopic parents compared with –1.13D (95% CI, –1.78 to –1.08) in children with no parental myopia. The adjusted odds ratio (OR) was 2.83 (95% CI, 2.47–3.24) in children with two myopic parents compared with no parental myopia. Conclusion: The study found a strong association between parental history of myopia and genesis of myopia in the offspring even after adjusting for environmental factors.